Exploring Neighborhood Bonds and Built-Environment on Parents’ Perceived Safety - Nirma Yossa (Eduvest - Journal of Universal Studies, 2024)
This study investigates parents’ perceived safety on neighborhood bonds and built-environment factors in letting their children roam outside unaccompanied using a qualitative lens. Based on interviews with parents in the Jakarta Greater Area, the research reveals that strong community cohesion and a perceived safe built-environment significantly enhance parents' sense of safety, thereby promoting children’s independent mobility. Conversely, neighborhoods with weaker neighborhood cohesion adding unmaintained built-environments such as and lack of playing field and pedestrian infrastructure heighten parents' fears about allowing unsupervised outdoor activities, thus limiting children's independence. Qualitative insights underscore that parents' primary concerns revolve around perceived risks from traffic and strangers when considering allowing their children to venture out alone. This research underscores the urgency for parents’ education and policy intervention planning that prioritizes walkable, safe routes, and safe parks and fosters strong community ties to promote children’s independent mobility.